Student records in the construction of student's problems - Silvina Cimolai (Arizona State University, 2014)
The role of student records is a scarcely considered issue in those researches that seek to analyze the daily practices carried out in schools, regarding students that are presenting some kind of learning or emotional problem. These records are more likely to be used by researchers as a source of information rather than being themselves the object of study. This research considered that student records were not only a document where professionals write about students and their interventions, but also a tool for configuring practices in certain ways. 127 student records from two district schools within the province of Buenos Aires were analyzed, documents and regulations related to the topic were collected, and interviews with a variety of professionals involved in writing and reviewing the records, were held. This paper presents the strategy for analysis and the categories developed in this exploratory study, concerning the different components of the records, agents and voices identified in them, instruments used, and labels and dimensions created to define the problems.